At the foot of the Ararat: Dambat/Tambat. A medieval Armenian ‘city’ on the foothills of Lesser Ararat mountain, Maku county, Iran - Khanmohammadi, Behrouz; Bodaqi, Ebrahim; Gasparro, Onofrio; Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
Maku County, located in the northwestern corner of Iran, has historically been a critical crossroads between major empires, including Persian, Armenian, and Turkish powers. Despite its strategic significance, the region’s challenging geography, characterized by rugged mountains and difficult terrain, has contributed to its marginalization in both Eastern and Western scholarly research. This article introduces a new study of the archaeological site of Dambat, previously known in the literature as Kharabe Zar (Dombad), which occupies a vast area on the southeastern slopes of Lesser Ararat, near the Iran-Turkey border. The site features extensive stone architecture, including defensive walls, storage wells, and underground shelters, suggesting a community engaged in pastoralism. Initial findings point to a society that combined agricultural and defensive strategies, though further archaeological excavations are essential to more fully uncover the settlement’s historical and cultural significance, and to address its role within the broader context of regional trade and interaction.